PENANGGULANGAN TINDAK PIDANA TERORISME MELALUI PENCEGAHAN PENDANAAN TERORISME DI PERKOTAAN DENGAN PENERAPAN SANKSI DOUBLE TRACK SYSTEM - Hariyono, Benny (Jurnal De Lege Ferenda Trisakti, 2025)
Rapid growth in urban areas often results in uncontrolled land use changes, ignoring the presence Terrorism is a relatively new crime regulated in a special law (Lex Specialis) which regulates terrorism after the Bali bombing in 2002 in Kuta, Bali. Seeing the motives of terrorism that often occur and target vital objects of the state and in big cities in Indonesia indicates that terrorism itself has been regulated in such a way that is structured, systematic and massive. The purpose of this study is to analyze the Countermeasures of Terrorism Through the Prevention of Terrorist Funding in Urban Areas with the Implementation of Double Track System Sanctions. This study uses the type of research used in this study is the type of normative legal research (Normative Legal Research). The results of the study indicate that through efforts to reform criminal law in the Terrorism Funding Law with the application of Double Track System sanctions, namely the imposition of sanctions along with criminal sanctions, rehabilitation or improvement can be carried out on the understandings of perpetrators of terrorism funding crimes that have been contaminated with teachings that are contrary to legal norms and the nation's ideology. so that it can suppress the development of terrorist organizations so that acts of terrorism that threaten vital economic and governmental objects in big cities can be overcome.